Fostering sustainable businesses in emerging economies : the impact of technology - Islam, Quazi Tafsirul; Goel, Richa; Singh, Tilottama (Emerald Publishing Limited, 2023)
Fostering Sustainable Businesses in Emerging Economies presents a series of case studies and exploratory studies, using quantitative analysis, scientific studies, and qualitative studies showing how innovation and technology enable emerging economies to achieve business sustainability and also achieve the Sustainable Development Goals (SDGs). Most of all, the authors answer the question: What are the most important lessons policymakers need to consider when promoting sustainable business development?